Larvicidal activities of 215 medicinal plants extracts against Aedes Aegypti from Bangladesh (Bangladesh Journal of Botany, 2025)
This study examined the effects of fresh crude extract from 215 plants on the mortality rate of third-instar larvae of Aedes aegypti after a 24-hour exposure. Twenty five plants demonstrated a high mortality rate  (up to 80%) at five different concentrations.  The LC50, LC90, and LC95 values of the tested plants showed that 15 plants were with 100% larvicidal potential. Stemona tuberosa showed the highest efficacy against Aedes larvae having LC50 = 3.78, LC90 = 7.51, and LC95 = 7.97, while Jatropha gossypifolia showed the lowest efficacy i.e., LC50 = 6.58, LC90 =11.23, and LC95 = 11.31. The extracts from Acmella radicans, Allium sativum, and Oxalis violacea exhibited a similar LC50 value of 3.99, indicating their high potency. Hence, the tested plants are a potential source of bioactive compounds that may work as a potential alternative to chemical mosquito larvicides.Bangladesh J. Bot. 54(1): 54-60, 2025 (March)